Pendampingan dan Pelatihan Pengadaan Produk Domestik Pariwisata Berbasis Zero Waste untuk Siswa MA/SMK - Muhammad Ramli; Zaitun Zaitun; Herman Supriadi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
This Community Service Program (PPM) is entitled "training and assistance in providing zero waste-based domestic tourism products" which aims to provide training to the millennial generation, both those still in junior high school and high school/vocational school/MA, to have awareness of the environment, soft skills, and have a sense of the tourism industry which it is hoped will be useful in the future. Besides students being taught how to produce domestic products, students are also taught about the importance of caring for the surrounding environment, especially plastic waste. This research was conducted using a qualitative descriptive method to record the reality of program implementation.